If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(9y+4)=(11y-14
We move all terms to the left:
(9y+4)-((11y-14)=0
We get rid of parentheses
9y-((11y-14)+4=0
| 4x-(-3)=-12 | | (3x+9=6x | | c/9−3=3 | | u=-4 | | -5=7+y/3 | | 3x-(5x-2)=-4 | | 2(4x-8)=3x+9 | | 44=n/3+11 | | -21=-v/4 | | -4-y=-5 | | 7x+3=2x+13+3+7+8+8+8+8+8+8+8+9-9 | | 2(33)+2e=776;e=355 | | .5(x-2)=1.5x-6 | | 2.50x+40=465 | | (10x+50)=10(x+50) | | 10u-20+61+49=180 | | 8(b+5)+5b=105 | | 6+2h=32 | | 3x+18-4=35 | | 2y+10+y+20+90=180 | | -15r=-135 | | 49=x7 | | -14+y=21 | | 168=8+8k | | m+8+3m=90 | | m/2−10=−10 | | s-4+58=180 | | 56=12x+20 | | -x/3=-38 | | 12x-2=-3x+10 | | 37=p+65 | | 9+2n-1=90 |